The Learning Outcomes Of Collaborative Writing In Enhancing College Students' Skills In Writing Essay - Senny Suzanna Alwasilah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study investigates the effect of collaborative writing on English as a Foreign Language (EFL) students' writing apprehension. The research explores whether engaging in collaborative writing activities influences students' levels of anxiety towards writing tasks and their perceived confidence in their writing abilities. qualitative data collection methods were employed, including pre- and a phase of teaching, and writing samples. The findings reveal a significant reduction in writing apprehension among students who participated in collaborative writing activities compared to those who worked individually. Collaborative writing not only provided students with opportunities to receive peer support and feedback but also fostered a sense of shared responsibility and accountability, leading to increased confidence in their writing abilities.